Decision Making System on The Selection of Gypsum According To User Demand Using Sugeno Method - Yosdarso Afero (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Gypsum is a ceiling that is often used by many people for housing parts that are on the ceiling of the house which serves to limit the height of a house or building that is useful for security, security and beauty in a room. Everyone has a desire to have a good gypsum building to be comfortable when in the house. The problem in the research is the lack of user knowledge in determining a good form of gypsum and having resistance for a long period of time. The purpose of this study is to assist users in selecting gypsum according to the wishes of the user. This study uses a decision-making system using the Sugeno method using the AND operator. Fuzzy logic has four work steps to obtain a decision-making system. The final output results obtained a value of 1 which is in the Interest Decision.